RAMATURGI TEATER REALISME SIASAT DRAMATIK DAN ARTISTIK MENCIPTA ILUSI REALITAS - Novianto, Wahyu (Acintya, 2018)
This research reveals the theatrical dramaturgy of realism and its staging strategies. As a dramaturgy study, history, theory, and theatrical conventions of realism are also revealed, from the beginning and development in the West to Indonesia. Furthermore, how a realism theater is created What are the dramatic and artistic tactics carried out by the director to bring the illusion of reality on the stage. This research is a literature review that makes books or other sources of literature the object of research.The results of the study explain that the history of the emergence of the theater of realism in the West is a rejection of the classical theater style that presents gods, fairies, and other mythological creatures. Theatrical realism conventions are themes around social life and psychology; the characters have sociological, psychological, and physiological dimensions; linear plot; settings are made static; absence of symbols; the fourth wall; and catharsis. The dramatic and artistic tactics carried out by the director are based on chaos, a personal experience experienced by the director.Key words: dramatic tactics, artistic tactics, realism, and the illusion of reality